Fear of falling and physical performance in elderly practitioners of physical activity Medo de cair e desempenho físico em idosos praticantes de atividade física - Hauser E.* (2015)
The goal of this study is to compare the physical capacities of sênior practitioners of physical activity accordingly with the preoccupation about the possibility of falling down. 144 seniors, practitioners of physical activity, have participated of this study, divided in two groups with and without fear of falling down. The preoccupation with the fear of falling down was assessed through Falls Efficacy Scale - International (FES-I-BRASIL) and the physical capacities (strength, flexibility, aerobic resistance and physical mobility) through the battery of motor test Senior Fitness Test. For the comiparison between the two groups the U Mann Whitney test was used. Significant difference between the groups, about the concern of the possibility to falling down, appeared in 15 of the 16 items assessed through the scale FES-I-BRASIL. About the physical capacities, significant differences were found in the variables: strength (inferior and superior members), physical mobility and aerobic resistance. Eve non active seniors a better physical capacity seem stobe a determinant factor regarding the fear of falling.